Fundamental principles of the Toyota Way and the Theory of Constraints: Comparative analysis and synthesis - De Almeida, Guilherme Venanzi; De Souza, Fernando Bernardi [UNESP]; Baptista, Humberto Rossetti; Gupta, Mahesh Chander; De Campos, Renato (Inderscience Publishers, 2018)
Several researchers have attempted to understand the essence of the principles that support Toyota Way and Theory of Constraints management philosophies, because they recognise such principles as central to explain their performance. For this reason, the objective of this study is to identify similarities and differences between the Theory of Constraints and the Toyota Way from a perspective on their essential fundamentals, as much as to identify gaps as opportunities for integration. From the methodological point of view, this is a theoretical-conceptual study based on the literature. Even though important differences have been identified, the results lead to significant similarities between the two forms of management. Such similarities can be the basis for the adoption of hybrid alternatives, which can expand their limits and favour their applicability as an integrated solution.
Keywords: Organisational culture; Principles; Theory of constraints; Toc; Toyota way; Tw